1999
DOI: 10.1110/ps.8.11.2529
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for triclosan activity involves a flipping loop in the active site

Abstract: Abstract:The crystal structure of the Escherichia coli enoyl reductase-NAD ϩ -triclosan complex has been determined at 2.5 Å resolution. The Ile192-Ser198 loop is either disordered or in an open conformation in the previously reported structures of the enzyme. This loop adopts a closed conformation in our structure, forming van der Waals interactions with the inhibitor and hydrogen bonds with the bound NAD ϩ cofactor. The opening and closing of this flipping loop is likely an important factor in substrate or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 17 publications
3
69
0
2
Order By: Relevance
“…In vitro, platensimycin binds to FabF relatively weakly, which led to the discovery that it preferentially targets the acyl-thioester intermediate of the FabF pathway (paralleling the cases of isoniazid [10] and triclosan [11], which act through binding with a FabI-NAD reaction intermediates). In a crystal structure of a Cys-163-Gln FabF mutant, which simulates this intermediate, platensimycin was observed to bind at the active site of FabF with the carboxylic acid group lying in the malonate binding site coplanar with the amide sidechain of Gln163 (Fig 3).…”
Section: New Natural Product Inhibitors Of Fatty Acid Biosynthesismentioning
confidence: 99%
“…In vitro, platensimycin binds to FabF relatively weakly, which led to the discovery that it preferentially targets the acyl-thioester intermediate of the FabF pathway (paralleling the cases of isoniazid [10] and triclosan [11], which act through binding with a FabI-NAD reaction intermediates). In a crystal structure of a Cys-163-Gln FabF mutant, which simulates this intermediate, platensimycin was observed to bind at the active site of FabF with the carboxylic acid group lying in the malonate binding site coplanar with the amide sidechain of Gln163 (Fig 3).…”
Section: New Natural Product Inhibitors Of Fatty Acid Biosynthesismentioning
confidence: 99%
“…FabH, a β-ketoacyl-acyl carrier protein synthase, is the bacterial condensing enzyme in Gram-positive and Gram-negative bacteria that initiates the cycle by catalyzing the first condensation step between acetyl-CoA and malonyl-ACP (139,140). Mycolic acid, one of the structurally largest fatty acids found in nature, is a vital cell wall component of the human tuberculosis strain of Mycobacterium tuberculosis.…”
Section: Thiolactomycin : Bacterial Fatty Acid Synthesis Inhibitormentioning
confidence: 99%
“…8 Many biochemical studies for the triclosan activity have been performed on the wild-type (WT) and mutated E. coli ENRs. [8][9][10][11][12][13][14][15][16] And as new bacterial ENR inhibitors, many ligands have been tested for their inhibitory activities. [17][18][19][20][21] At first in 1996 Rice's group used diazaborine derivatives as the antibacterial candidate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…2,17 But these ligands are known to be toxic compounds, and it was investigated on molecular basis study that a flipping loop (I192-S198) of E. coli ENR is involved in the active site with triclosan. 14 In 2001 Heerding's group reported that the 1,4-disubstituted imidazoles are critical and effective inhibitors to FabI activity, 18 and Seefeld's group tested 2,9-disubstituted 1,2,3,4-tetrahydropyrido [3,4-b] It is very important to understand the functional groups and structures of good ligands and the important amino acid residues of the active site of ENR where the ligands would bind with different binding efficacies. Detailed understanding of the structure and energy relationship of these ENR inhibitors could help the design of new and improved ENR inhibitors.…”
Section: Introductionmentioning
confidence: 99%